WiFi network for long distances applications - Saeed, Rashid Abdelhaleem (IIUM Press, 2011)
The needs for bridging of digital divide in the rural communities and the economics of currently available broadband access technologies have motivated us for innovation and deployment of the new system designs and applications. The widely available and flexible WiFi technique meets the cost and suitability targets for the rural broadband applications. To cope with the special requirements of rural communication. amendments of 802.11 standards at the MAC protocol level has been introduced. These amendments are important due to the shortcomings of WiFi over long distances under the power constraints. This chapter proposes a new 802.11 point-to-multipoint (PMP) technique based on TDD/TDMA technique by using one of the access points in the system as centralized/gateway point to the other APs. The discussion includes the TDMA design and, architecture on top of the conventional 802.11 MAC. The protocol convergence at the gateway between the access network and the backhaul is also presented. The simulation results present the performance analysis and validate the efficiency of the proposed scheme